KUALITAS PELAYANAN DI PUSKESMAS UJUNG BATU KAB. ROKAN HULU PROVINSI RIAU (STUDI KASUS PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) - Fara Dea Orisa; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The increasing demands for quality public health services, the service function should be improved to provide patient satisfaction. Quality of service is a form of patient assessment of the level of service received by the service expected, most of the government agencies in Indonesia has been implementing service with good but not maximized. But, at the health center Ujung Batu not implement the service properly. The facilities provided by these health centers are still lacking and quite slow in providing services, employee health centers are also less friendly in providing services to patients, as well as employees of the health center are also less response to the complaints of patients treated at this health center. So Puskesmas Ujung Batu has not been able to do a good job. The purpose of this study was to determine the quality of health services at the district health center. Ujung Batu and determine the factors that influence it.Researchers used the theory of Agus Dwiyanto where quality of service can be determined by the dimensions of the officer attitude, procedure, time, facilities, and services. This study uses qualitative exploratory methods, techniques collecting data through observation and interviews in which the parties - the parties involved in this study as an informant.The results of this study indicate that the PHC Ujung Batu had poor service quality in serving the community and not in accordance with what is expected of society. Starting from facilities that are incomplete, slow employees in providing services, employee health centers are also less friendly, employees are less in response to patient complaints. It is not yet meet all the indicators that measureJom FISIP Vol 3 No.2 – Oktober 2016 Page 2the quality of service is good. Factors that affect the quality of services in health centers Ujung Batu are infrastructure, human resources, and leadership.Keywords: quality of care, health services